The Effect of Chemical Coagulant Dosages on the Removal of Turbidity from Wastewater - Estabraq Ali Hameed; Rodhan Abdullah Salih; Ali Mohammed Saleh; Hussein M. Issa; Mahmod A. Abdulqader (AUIQ Complementary Biological System)
This research aims to compare different coagulants, which are alum, ferric chloride, and polyaluminum chloride, in treating turbidity in water. The objective is to determine the optimal dosage of each coagulant for the removal of visible turbidity at levels of 400, 85, 70, and 40 NTU, respectively. The study also considers the (pH) levels resulting from the addition of coagulants, measures the percentage of remaining materials from the used coagulant (sulfates from alum, chloride from ferric chloride, and chlorides from polyaluminum chloride). A 1000 l tank and its components were controlled by adding the desired pollutants (clay and plant impurities) and known, Oxygen Demand (BOD), 20 mg/l. The experimental results demonstrate that ferric chloride has an advantage in turbidity removal, especially when the standard turbidity value is 5 NTU. The optimal dosage is found to be 23 mg/L for 400 NTU, 20 mg/L for 85 NTU, 17 mg/L for 70 NTU, and 10 mg/L for 40 NTU. Therefore, the results of pH were improved from 7.0 to 7.8, as well as ferric chloride from 12 to 17 mg/l for poly aluminum chloride. The study reveals a significant increase in chloride ions with the addition of ferric chloride and polyaluminum chloride, while there is a slight increase in sulfate ions with the addition of alum.